Liberalism and the Challenges of Democracy in Nigeria - Oyigebe , Peter Luke; Yakubu, Muazu Adamu (Kashere Journal of Politics and International Relations, 2023)
The purpose of this paper is to attempt a critical appraisal of the pace, practice, pattern, priorities, problems and prospects of Nigerian democracy. While it remains true that Nigeria is governed by democratically elected leaders at the federal and state levels, Nigeria is yet to institutionalize democracy after a century of existence as a political entity. The paper discusses some of the impediments to the institutionalization of democracy in Nigeria after more than half a century of political independence. Some of these are the country’s colonial background interspersed by vagaries engendered by deep-rooted ethnicity; complacent and spendthrift leadership. The paper obtained its data from secondary source materials and employs the historical method of data analysis simple descriptive collation and analysis of historical data. The study discovered that though, democracy in Nigeria is flawed and threatened by both internal and external factors such as corruption and external interference but this does not negate the fact that it still preferred democracy more than military dictatorship and authoritarianism. Some of the recommendation provided by this study to help solve some of encumbrances hindering the democratic consolidation of the country includes; the fact that Nigeria as a country needs a democracy capable of guaranteeing maximum practice of freedom at its peak by the citizens without any fear of oppression.